Rationalizing the Binding Modes of PET Radiotracers Targeting the Norepinephrine Transporter - Anna Tutov; Xinyu Chen; Rudolf A. Werner; Saskia Mühlig; Thomas Zimmermann; Naoko Nose; Kazuhiro Koshino; Constantin Lapa; Michael Decker; Takahiro Higuchi (MDPI AG, 2023)
Purpose: A new PET radiotracer 18F-AF78 showing great potential for clinical application has been reported recently. It belongs to a new generation of phenethylguanidine-based norepinephrine transporter (NET)-targeting radiotracers. Although many efforts have been made to develop NET inhibitors as antidepressants, systemic investigations of the structure-activity relationships (SARs) of NET-targeting radiotracers have rarely been performed. Methods: Without changing the phenethylguanidine pharmacophore and 3-fluoropropyl moiety that is crucial for easy labeling, six new analogs of 18F-AF78 with different meta-substituents on the benzene-ring were synthesized and evaluated in a competitive cellular uptake assay and in in vivo animal experiments in rats. Computational modeling of these tracers was established to quantitatively rationalize the interaction between the radiotracers and NET. Results: Using non-radiolabeled reference compounds, a competitive cellular uptake assay showed a decrease in NET-transporting affinity from meta-fluorine to iodine (0.42 and 6.51 µM, respectively), with meta-OH being the least active (22.67 µM). Furthermore, in vivo animal studies with radioisotopes showed that heart-to-blood ratios agreed with the cellular experiments, with AF78(F) exhibiting the highest cardiac uptake. This result correlates positively with the electronegativity rather than the atomic radius of the meta-substituent. Computational modeling studies revealed a crucial influence of halogen substituents on the radiotracer-NET interaction, whereby a T-shaped π-π stacking interaction between the benzene-ring of the tracer and the amino acid residues surrounding the NET binding site made major contributions to the different affinities, in accordance with the pharmacological data. Conclusion: The SARs were characterized by in vitro and in vivo evaluation, and computational modeling quantitatively rationalized the interaction between radiotracers and the NET binding site. These findings pave the way for further evaluation in different species and underline the potential of AF78(F) for clinical application, e.g., cardiac innervation imaging or molecular imaging of neuroendocrine tumors.